Effective indicators of healthy cities in facing natural disasters (epidemics and diseases) - Al-Budairi, Bahaa; Al-Rikabi, Nada (Journal of Planner and Development, 2023)
The excessive and rapid urban growth witnessed by most cities in the world can be a cause of diseases and epidemics, especially those problems related to population, which include problems of transportation and increase in density in the centers, in addition to the lack of interest in planning and designing those cities to take into account the health aspect of the city and obtain The health well-being of the population, and each of these problems has negative effects on health in general and on human health in particular through its prevalence. Therefore, many concepts that serve as a tool for achieving public health and the physical health of the population have emerged, including the concept of city health, which is defined as cities that improve their environment and develop their resources by achieving health as urban. And the issue that must be achieved in the city and at various levels, hence the research problem. The lack of clarity of the indicators of healthy cities affecting the achievement of the health dimension of the population, and accordingly the goal of the research was determined to study the concept of healthy cities and their spatial relationship to the spread of diseases and epidemics, in order to reach effective indicators and results that contribute to reducing the speed of the spread of these diseases and epidemics, as the research assumes that: Principles can That the foundations of the concept of healthy cities have a clear impact and role in reducing epidemics. In order to achieve the goal of the research, the concept of healthy cities and the concept of epidemics and their impact on the city were dealt with in order to reach clear relationships and results that can be applied to the Iraqi city (Al-Ghadeer Village Residential Complex in Al-Najaf Al-Ashraf), where the most important results were movement, transportation, density and diversity, and each of these concepts has mechanisms for its application .